Canthonini (Scarabaeidae: Scarabaeinae) of Gondwana : comparison of male genitalia evolutionary trends and phylogeny - Scholtz, Clarke H. (University of Pretoria, 2015)
Thesis (DPhil)--University of Pretoria, 2015.